The Process of Surveying Maquettes in Car Design (diségno, 2020)
This work grew out of a desire to investigate the digital surveying process used in phases to define the concept of a morphologically complex product such as an automobile. This investigation was conducted by analysing the final steps of the first ten editions of the Specialized Master course in Transportation & Automobile Design at Politecnico di Milano University. In analysing the procedures to create the presentation models starting with clay studio models, four protocols were standardized and compared. Following this, some suggestions and guidelines were summarized to ensure that faithfulness to the design intent during the process would not fail. The ultimate goal of this work is to highlight the critical aspects of a process that is based on a quantitative method (the digital survey), but that requires a qualitative approach to be truly effective.
Keywords: 3D scan; car design; car concept; 3D modelling; physical modelling